2021
DOI: 10.1186/s12877-021-02498-y
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation potential in older people living with frailty: a systematic mapping review

Abstract: Background Following periods of acute ill-health and injury, older people are frequently assessed and provided with rehabilitation services. Healthcare practitioners are required to make nuanced decisions about which patients are likely to benefit from and respond to rehabilitation. The clinical currency in which these decisions are transacted is through the term “rehabilitation potential”. The aim of this study was to explore information about rehabilitation potential in older people to inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
(238 reference statements)
0
8
0
Order By: Relevance
“…As reported by ISTAT [ 26 ], the presence of health problems and the loss of autonomy determine a growth in healthcare consumption, especially after the age of 75, with increasing recourse to MSs and hospital admission. Moreover, frail older people with functional limitations use rehabilitation interventions (as reported by our respondents), which Cowley and colleagues [ 62 ] describe as having a great potential for recovery, especially after periods of acute illness or hospitalization. In this regard, a review evaluating 51 articles on the topic [ 63 ] highlighted that after hospitalization, 11% of older patients aged 75 years and over, are referred to rehabilitation facilities.…”
Section: Discussionmentioning
confidence: 98%
“…As reported by ISTAT [ 26 ], the presence of health problems and the loss of autonomy determine a growth in healthcare consumption, especially after the age of 75, with increasing recourse to MSs and hospital admission. Moreover, frail older people with functional limitations use rehabilitation interventions (as reported by our respondents), which Cowley and colleagues [ 62 ] describe as having a great potential for recovery, especially after periods of acute illness or hospitalization. In this regard, a review evaluating 51 articles on the topic [ 63 ] highlighted that after hospitalization, 11% of older patients aged 75 years and over, are referred to rehabilitation facilities.…”
Section: Discussionmentioning
confidence: 98%
“…Patient characteristics, that may inform predictions of rehabilitation potential [11], were identified from medical notes and electronic hospital records by the research team. These included: age, gender, ethnicity, residential and cohabitation status, co-morbidities, medications, cognition, frailty status, pre-admission mobility, ADL abilities and reasons for admission to acute care.…”
Section: Data Collectionmentioning
confidence: 99%
“…A recent systematic mapping review found [11] found that concepts of rehabilitation potential in older people could encompass prognostication (a prediction of what could be achieved with rehabilitation programmes) and outcome measurement (a retrospective understanding of what had been achieved) but that assessments tend to be based upon a snapshot of older people's abilities rather than taking account of the dynamic nature of frailty and rehabilitation practice. A qualitative focus group study found that rehabilitation potential assessments in the acute setting coalesced around three clinical questions -"will it work?…”
Section: Introductionmentioning
confidence: 99%
“…7 A systematic review by the same group found the phrase, rehabilitation potential, encompassed ‘two different but interrelated concepts of prognostication and outcome measurement’. 8…”
Section: Introductionmentioning
confidence: 99%